2019
DOI: 10.1002/ajp.22951
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in scent‐marking in captive red‐ruffed lemurs

Abstract: Primate chemical communication remains underappreciated, as primates are considered to rely on other sensory modalities. However, various lines of evidence suggest that olfaction plays an important role in primate societies, including the conspicuous scent-marking behavior of many strepsirrhines and callitrichines. Although lemurs typically show scent-marking, little is known about this behavior in red-ruffed lemurs (Varecia variegata rubra). We combined behavioral observations and semiochemistry analyses to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 57 publications
(86 reference statements)
3
37
0
Order By: Relevance
“…Among the acids (2-methyl propanoic acid, butyric acid, 2-methyl hexadecanoic acid, and benzoic acid), we found the compound butyric acid that is one of the five aliphatic acids, named “copulins”, which were also found in women’s vaginal secretions and considered to contribute to making these vaginal secretions attractive to males 89 . Likewise, methoxy-phenyl-oxime was identified in human axillary sweat 90 , and reported as a minor constituent of essential oils and aromatic extracts 91 ; conversely, the other compound which we found with highest abundance and most change from sample to sample, p -cresol, has previously been identified in female scent-marks by red-ruffed lemurs 84 and capuchin monkeys 92 as well as a component of the female sex pheromone in the horse ( Equus caballus ). Additionally, the compounds benzoic acid, hexanal and 1-Octen-3-ol are encountered in odour secretions used to scent-mark by several non-primate mammals (e.g., lions ( Panthera leo ), African wild dogs ( Lycaon pictus ), gray wolves ( Canis lupus ), house mice ( Mus musculus ), red foxes ( Vulpes vulpes )) (reviewed in 93 ) and primates (e.g., aye-ayes ( Daubentonia madagascariensis ) 94 , red-ruffed lemurs 84 , ring-tailed lemurs 43 , Coquerel’s sifakas 83 , common marmosets 95 ) (see Table 2 for details).…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…Among the acids (2-methyl propanoic acid, butyric acid, 2-methyl hexadecanoic acid, and benzoic acid), we found the compound butyric acid that is one of the five aliphatic acids, named “copulins”, which were also found in women’s vaginal secretions and considered to contribute to making these vaginal secretions attractive to males 89 . Likewise, methoxy-phenyl-oxime was identified in human axillary sweat 90 , and reported as a minor constituent of essential oils and aromatic extracts 91 ; conversely, the other compound which we found with highest abundance and most change from sample to sample, p -cresol, has previously been identified in female scent-marks by red-ruffed lemurs 84 and capuchin monkeys 92 as well as a component of the female sex pheromone in the horse ( Equus caballus ). Additionally, the compounds benzoic acid, hexanal and 1-Octen-3-ol are encountered in odour secretions used to scent-mark by several non-primate mammals (e.g., lions ( Panthera leo ), African wild dogs ( Lycaon pictus ), gray wolves ( Canis lupus ), house mice ( Mus musculus ), red foxes ( Vulpes vulpes )) (reviewed in 93 ) and primates (e.g., aye-ayes ( Daubentonia madagascariensis ) 94 , red-ruffed lemurs 84 , ring-tailed lemurs 43 , Coquerel’s sifakas 83 , common marmosets 95 ) (see Table 2 for details).…”
Section: Discussionsupporting
confidence: 49%
“…Likewise, methoxy-phenyl-oxime was identified in human axillary sweat 90 , and reported as a minor constituent of essential oils and aromatic extracts 91 ; conversely, the other compound which we found with highest abundance and most change from sample to sample, p -cresol, has previously been identified in female scent-marks by red-ruffed lemurs 84 and capuchin monkeys 92 as well as a component of the female sex pheromone in the horse ( Equus caballus ). Additionally, the compounds benzoic acid, hexanal and 1-Octen-3-ol are encountered in odour secretions used to scent-mark by several non-primate mammals (e.g., lions ( Panthera leo ), African wild dogs ( Lycaon pictus ), gray wolves ( Canis lupus ), house mice ( Mus musculus ), red foxes ( Vulpes vulpes )) (reviewed in 93 ) and primates (e.g., aye-ayes ( Daubentonia madagascariensis ) 94 , red-ruffed lemurs 84 , ring-tailed lemurs 43 , Coquerel’s sifakas 83 , common marmosets 95 ) (see Table 2 for details). The compound benzaldehyde is considered a crucial putative semiochemical occurring at all ancestral nodes leading to both urine and glandular markers in many strepsirrhine species 96 ; this compound has also been found in scent gland secretions released by ayes-ayes 94 , red-ruffed lemurs 84 , common marmosets 95 , capuchin monkeys 92 , emperor tamarins 97 , Weddell’s saddleback tamarins 97 , owl monkeys (where the presence of this compound has also been validated with internal standards) 57 and mandrills 39 , 40 , and acts as a sex pheromone in other mammals and as an alarm pheromone in invertebrates such as stingless bees ( Tetragonisca angustula ) (reviewed in 73 ).…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Interestingly, we found that scent enrichment exerted both behavioural and physiological effects on both red-ruffed lemurs and Lar gibbon. While the use of chemical communication and olfactory signals in lemurs has long been established [51][52][53], apes are commonly considered microsmatic. However, accumulating evidence seems to suggest that apes may also rely on olfactory signals and chemical communication.…”
Section: Discussionmentioning
confidence: 99%
“…Although primates have traditionally been considered to be “microsmatic” with a simultaneous amplified emphasis on vision (Dominy & Lucas, 2001; Fornalé et al, 2012; Gerald, 2003), several studies suggest that chemical communication is important also for primate species (reviewed by Drea, 2020). Particularly, it is established that some species rely heavily on olfaction in addition to vision and auditory senses; for instance, this is the case of several lemurs (Gould & Overdorff, 2002; Janda et al, 2019; Scordato & Drea, 2007) and squirrel monkeys (Laska et al, 2000). This would explain the significant impact of our scent enrichment on red-ruffed lemurs, rather than the other study species for which no such response was observed, as lemurs have retained a greater olfactory complexity than other lineages such as monkeys and apes.…”
Section: Discussionmentioning
confidence: 99%